2007
DOI: 10.2320/matertrans.mrp2006634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sodium Gluconate by Bi Promoted Pd/C Catalyst

Abstract: Bi promoted Pd/C catalyst (Bi-Pd/C) was prepared and evaluated for glucose oxidation in this paper. Reaction rate depends on Bi and Pd ratio on activated carbon. Best promotion effect was got when PdCl 2 to Bi (NO) 3 Á5H 2 O weight ratio was 1 to 3 during catalyst preparation. Compared with other noble metal catalyst, the reaction time was reduced and Bi prevented the Pd/C deactivation during this reaction. The reaction cycle for this catalyst was increased a lot compared with other Pd/C catalyst. Through XPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Bimetallic catalysts modified with Pt and Pd have been investigated to inhibit rapid deactivation. However, noble metal-supported catalysts are easily poisoned by oxygen molecules, generally showing low reusability. It was found that the addition of Bi as a promoter can not only delay the deactivation of catalysts but also prevent excessive oxidation of Pd particles partially and enhance the reusability of the catalyst. Due to the excessive oxidation of Pd particles, the reaction rate was low over the unpromoted Pd-based catalyst, although it was active in glucose oxidation to gluconic acid. The occurrence of side reactions ascribing to the excessive oxidation of Pd particles also decreased the selectivity of the desired gluconic acid.…”
Section: Thermal Catalytic Transformations Of Biomass-derived Glucosementioning
confidence: 99%
“…Bimetallic catalysts modified with Pt and Pd have been investigated to inhibit rapid deactivation. However, noble metal-supported catalysts are easily poisoned by oxygen molecules, generally showing low reusability. It was found that the addition of Bi as a promoter can not only delay the deactivation of catalysts but also prevent excessive oxidation of Pd particles partially and enhance the reusability of the catalyst. Due to the excessive oxidation of Pd particles, the reaction rate was low over the unpromoted Pd-based catalyst, although it was active in glucose oxidation to gluconic acid. The occurrence of side reactions ascribing to the excessive oxidation of Pd particles also decreased the selectivity of the desired gluconic acid.…”
Section: Thermal Catalytic Transformations Of Biomass-derived Glucosementioning
confidence: 99%
“…Bian et al [16] reported the use of Bi-Pd/C catalyst as a very promising and effective catalyst for industrial production of sodium gluconatefrom glucose with the advantage of simple and green chemical process compared with enzymatic process. For industrial applications, cost effective and lifetime oroutput for per kilogram catalyst is a crucial point.…”
Section: Introductionmentioning
confidence: 99%